Investigating the Village-based Tourism Economic Impact - Desi Ilona; Z Zaitul; Neva Novianti (UPI YPTK Journal of Business and Economics, 2022)
Many studies have been documented that tourism economic impact is a determinant of community support toward tourism development. However, there is a lack of study investigating tourism economic impact on village-based tourism. This study investigates the relative important index of the item offered by previous literature. Besides, this study also examines different means from different respondents: gender, education, and age. Forty-seven respondents have participated in this study. The validity and reliability test is run before the items are ranked using the relative important index (RII). Mann-Whitney U test has applied any difference of means value between woman and man. Moreover, the Kruskal-Wallis test is employed to determine any difference of means value among different levels of respondent education. The result shows that all items are valid and reliable. This study concludes that the first rank is variable 1 (village-based tourism increased job opportunities for village communities) with a relative important index of 0.898. Besides, six items have no mean value difference between man and woman, except for variable 5 (village-based tourism given economic benefit to village people). Its asym significance of Mann-Whitney U asym significance is lesser than 0.05. Further, respondent education and age category also have no difference in mean value using the Kruskal Wallis test. This study implies that the tourism economics impact for village-based tourism can be used for further studies.